Q-band polarizers for the LSPE-Strip correlation radiometric instrument. (1st June 2022) - Peverini, O.A.; Lumia, M.; Farooqui, Z.; Addamo, G.; Virone, G.; Paonessa, F.; Ciorba, L.; Zannoni, M.; Gervasi, M.; Franceschet, C.; Bersanelli, M.; Mennella, A.; et al.
Abstract: This paper reports the design, manufacturing and testing of the cluster of polarizers developed for the LSPE-Strip correlation receiver array working in the Q band (39–48 GHz). Since the LSPE experiment targets the measurement of the very faint B-mode component of the Cosmic Microwave Background, the electromagnetic design of the polarizers was conceived in view of minimizing the measurement uncertainties introduced by the polarizers in the LSPE-Strip dual-circular-polarization correlation receiving chain. To this end, the main figures-of-merit of the LSPE-Strip polarizers were derived in terms of the Mueller sub-matrices relating the relevant input and output Stokes parameters. As a result, a dual-ridge layout, in which stepped-ridge discontinuities are interleaved with grooved cavities, was selected. The heights of both the stepped discontinuities and the grooved cavities were considered as design degrees of freedom in order to minimize the differential phase-error between the two principal polarizations of the polarizer w.r.t. the ideal 90-deg value. The latter condition is the one required for converting the incoming circular polarizations into two linearly polarized ones. The polarizer design allows for a complete manufacturing route (mechanical layout, machining process and assembling) exhibiting high accuracy (< 10 μm) for all the units. As a consequence, the measured performance of the whole polarizer cluster is in tight agreement with predictions. Notably, the in-band mean value of the spurious conversion from the total intensity I to the two linearly polarized Stokes parameters Q and U introduced by the polarizers is smaller than -28 dB (mean value of fifty-one polarizers) with a standard deviation less than 1 dB.